INFRASTRUCTURES OF MANIPULATION - Iliadis, Andrew; Tripodi, Francesca; Dave, Aashka; Jones, Leslie Kay; Acker, Amelia; Ford, Heather (AoIR Selected Papers of Internet Research, 2023)
This panel presents research on web and information infrastructures used for manipulative purposes. In contrast to platform manipulation (Woolley & Howard, 2018; Benkler et al., 2018), where users such as bad actors seek to gamify and exploit the weaknesses of online social media platforms like Twitter and TikTok, the papers in the present panel describe studies where web or information infrastructures such as those involved in search and information retrieval are manipulated to alter or produce facts (rather than social commentary on facts). For example, studies have shown how infrastructures like Google Search are manipulated by conservative elites (Tripodi, 2022), how anonymous editors use Wikidata to revise the distribution of information related to political protest movements (Ford, 2022), and how administrators harness information schemas to improve the findability of their advertising content (Iliadis, 2022). In these areas and more, web and digital infrastructures are being manipulated to serve the interests of politically motivated actors (Acker, 2018; Acker & Donovan, 2019).Infrastructures typically refer to shared public services like sewers, telephone poles, and electricity. According to Bowker et al. (2010, p. 98), information infrastructure refers to “digital facilities and services usually associated with the internet.” Information infrastructures are thus enabling resources, in network form, whose key role is that of a distributor, but rather than goods or services, information infrastructures distribute “knowledge, culture, and practice” (Bowker et al., 2010, p. 114). Such structures do this through their development of ontologies or classification schemes that enable dividing the world into categories or, through their application to large data sets, by offering an enormous, open store of data that can be used by others for a variety of purposes, such as retrieving facts and sharing information. Recently, several scholars have elaborated on the political nature of such infrastructural processes of digitization and datafication, including in the domains of archiving and preservation (Thylstrup, 2018, 2022), governance and management (Flyverbom & Murray, 2018), metrics and sorting (Alaimo & Kallinikos, 2021), and the creation of global ontologies for things like web search (Iliadis et al., 2023) and surveillance services (Iliadis & Acker, 2022).Manipulation of social media content and messaging is likewise a major research area over the last several years owing to the prevalence of online misinformation and disinformation campaigns (Reagle, 2016; Paris, 2021; Culloty & Suiter, 2021), particularly those associated with electoral politics (Tucker & Persily, 2020) and health misinformation (Keselman et al., 2022). Yet, online manipulation is not a new phenomenon and has long been discussed as a feature of the web in the context of the history of trolling, abuse, and hate (Phillips, 2015, 2019). Manipulation is thus a multivalent concept and is found in several domains which share the notion that manipulation is related to the altering, editing, treating, controlling, and influencing of content and messages for the purpose of misleading individuals. Historically, though, less attention has focused on manipulation as it has been mobilized infrastructurally, particularly with respect to the information infrastructures that transmit content and messages. Infrastructures should be understood here in a broad sense as undergirding the communication structures that transmit messages and content. Such infrastructures can be found in computer science, news and journalism, government, policy, and other areas where messaging is organized using some form of schema, whether it be technical, linguistic, financial, or otherwise.The first paper uses interviews to highlight the “importance of abortion-related web search and whether or not that system has been manipulated by actors trying to prevent abortion access.” The paper “examines how people (users) search for information about abortion, how organizations (content providers) utilize search engine optimization to reach potential users, and how advertisers try to attract visitors.” The second paper uses autoethnography and process tracing with respect to “the AP African American Studies debacle in order to elucidate digitally mediated disinformation as a strategy for stoking moral panic and thereby gaining widespread public buy-in to the establishment of educational censorship infrastructure.” The third paper analyzes Palantir as a surveillance platform that shapes and is shaped by infrastructures of manipulation. The paper “provides a method for researching companies like Palantir and its surveillance infrastructures” through digital media archiving of “over 600+ documents which have been stored, cleaned, annotated, and uploaded into an online digital archive that will be publicly available for media researchers to study.” The fourth and final paper is “an ethnographic study of a single Wikipedia article and how it evolved over the course of a decade” in the context of political revolutons. The paper describes “a framework for understanding new methods of controlling facts in the context of automated knowledge products” and “the importance of semantic infrastructure to new methods of control and influence on Wikipedia and the wider knowledge infrastructures that are increasingly dependent on it.”